A short review of isoindigo acceptor for conjugated polymeric photovoltaics - Shu, Er Tan; Wahidah Zabidi; Mohd Sani Sarjadi (Universiti Malaysia Sabah, 2017)
This paper focused on the recent development of conjugated polymers that contains isoindigo as acceptor moiety in the application of copolymeric solar cell. In the past decade, various modifications have been done either on the isoindigo acceptor itself or incorporated the isoindigo with different donor moieties. Recently, the power conversion efficiency (PCE) of this isoindigo-based polymeric photovoltaics have achieved up to ~7%. Hence, it is a promising acceptor for the photovoltaics and is expected to break through the recent PCE achievement in the future. This review briefly summarized the structures and properties of the isoindigo-based polymers that have been investigated by the past researches.